2001
DOI: 10.1300/j074v13n02_06
|View full text |Cite
|
Sign up to set email alerts
|

Risk Status Related to Knowledge of Osteoporosis in Older Women

Abstract: Additional educational programs might increase awareness of risk factors and behaviors likely to enhance bone health. All older women should be encouraged to initiate discussion regarding osteoporosis with their health care providers. Physicians, nurses, social workers, and others also should assess their client's knowledge of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 2 publications
3
16
1
2
Order By: Relevance
“…perceived seriousness of a disease, perceived susceptibility of a disease, perceived benefits of positive attitude and practice and lastly perceived barriers that might restrain an individual to make positive changes [22]. Similar to findings of other studies, a majority of the participants in the present study have identified lack of calcium and dairy products as a risk factor for osteoporosis while minority had identified genetics or family history as risk factor for osteoporosis [15].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…perceived seriousness of a disease, perceived susceptibility of a disease, perceived benefits of positive attitude and practice and lastly perceived barriers that might restrain an individual to make positive changes [22]. Similar to findings of other studies, a majority of the participants in the present study have identified lack of calcium and dairy products as a risk factor for osteoporosis while minority had identified genetics or family history as risk factor for osteoporosis [15].…”
Section: Discussionsupporting
confidence: 81%
“…However, there are some that are worth mentioning their limitations. Most of the studies that have been conducted previously do not use a validated questionnaire to assess KAP [10,[11][12][13][14] and the main focus of those studies was women who were already suffering from osteoporosis [15]. It must be noticeable that those who are already suffering from a disease or under treatment of a particular disease would have better knowledge of disease as they are in direct contact with health care professionals.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study conducted by Gurryet et al identified the premature menopause and race as biggest risk factors that do not correspond with our findings. 18 also supports an association between soft drinks consumption and decreased bone mineral density. 19 In a study done on 270 women in Turkey by Tumer and et al, it was revealed that more than 40% of women did not know the risk factors for the disease.…”
supporting
confidence: 62%
“…BMD was given as absolute values in g/cm 2 , and as Z and, T-score values. The Z-score value corresponds to the number of standard deviations from the mean value that was defined by the range of BMD of an ethnically comparable age and gender-matched reference population.…”
Section: Dxa Measurementsmentioning
confidence: 99%
“…Therefore, information of elderly persons to increase awareness of osteoporosis is important. Previous works show that health promotion programs can help to reach populations at risk for osteoporotic fractures, thus, reducing morbidity and mortality [1][2][3]. Information about osteoporosis and increased fracture risk both for populations as well as individual patients and their treating practitioners is an important part of prevention programs [4,5].…”
Section: Introductionmentioning
confidence: 99%